PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN PANGGUNGREJO MELALUI MOTIVASI - Hermanto, Hermanto; Muhinghar, Muninghar; Kartika, Chandra (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
The purpose of this study is to describe the work environment, work discipline, work motivation and performance of employees of the Panggungrejo District Office, Pasuruan City, in addition to testing and analyzing the influence of the work environment and work discipline on employee performance through work motivation. The population of this study were all employees of the Panggungrejo District Office, Pasuruan City, totaling 44 people. The sample in this study was the entire population, namely 44 using total sampling. The results of the study concluded that the work environment, work discipline, work motivation, and employee performance in the Panggungrejo District, Pasuruan City, were in the high category. The work environment has a significant influence on work motivation. Work discipline has a significant influence on work motivation. Work environment has no significant effect on performance. Work discipline has a significant influence on performance. Work motivation has a significant influence on performance. The work environment has a significant influence on performance through work motivation. Work discipline has a significant influence on employee performance through work motivation.